PENGENALAN DAN PEMBELAJARAN (HANDS-ON) PERTOLONGAN PERTAMA PADA KASUS GAWAT DARURAT DAN BANTUAN HIDUP DASAR (BHD) - Parami, P. (Buletin Udayana Mengabdi; Vol 23 No 2 (2024): Buletin Udayana MengabdiDO - 10.24843/BUM.2024.v23.i02.p02, 2023)
Emergency condition that requires basic life support & first aid could happen everywhere. The high incidence of emergency cases in Bali contradicts the low number of trained non-healthcare providers in regard to basic life support and first aid. School as a public place is the target for basic life support training and public access to an automated external defibrillator (AED) for the lay rescuer. This training is provided for making cardiac emergency response plans available for everyone inside the school area. This introduction and simulation for an emergency case with basic life support, first aid, and public access AED has held at SMA Negeri 3 Denpasar on the 4 th of September 2021 with hybrid adjustment due to the covid pandemic. The aim of this public training is for improving students’ knowledge and skills to provide basic life support, and first aid and to use the AED for emergency cases appropriately. The mean pretest score for knowledge is 50,8 and the post-test is 76,4 showing a 25,6 augmentation. All participants mentioned that this public training was useful and increased their skills. Eighty percent of participants suggested that this training should be held annually. Keywords: basic life support, lay rescuer, school.